Towards a Higher Education curriculum for South African ecommerce entrepreneurs - Budree, Adheesh (School of Education, 2025)
This study investigated the development of an inclusive curriculum for eCommerce entrepreneurship in South Africa. The main research question posed in this study was ‘How can an inclusive curriculum be developed to support the development of eCommerce entrepreneurs in South Africa?' The research question was broken down into three sub-questions addressing three domains, namely empirical, actual and real in the context of a South African eCommerce entrepreneurship curriculum, in line with a postcolonial critical realism theory as a theoretical framework. The study sought to identify the development principles associated with a curriculum based on the skills and competencies required by eCommerce entrepreneurs within the context of conducting online business in South Africa that allowed them to not only fully comprehend the markets they operate in, but to also thrive within these markets and adjust to evolving circumstances. This required the exploration of the attributes needed for successful eCommerce entrepreneurs within the context in which the entrepreneur exists which then informs the curriculum development process required to develop a curriculum that addresses the needs of up-and-coming eCommerce entrepreneurs in the country. Subject-matter experts in eCommerce entrepreneurship involved with curriculum development and the eCommerce industry were interviewed to analyse the requirements for an inclusive eCommerce entrepreneurship curriculum in South Africa. A thematic analysis was conducted to extract the main themes arising from the interviews. These were aligned with a conceptualised theory incorporating postcolonial critical realism which was used as the theoretical framework to interrogate the phenomenon. The themes were then analysed to derive design principles. By integrating these principles, the curriculum design for eCommerce entrepreneurship in South Africa can be both transformative and responsive to the needs and realities of a postcolonial society, leveraging education as a tool for empowerment and social change. The findings of this study are aimed at informing curriculum development across South African Higher Education institutions, both in the public and private sectors, which could positively impact on both higher education policy in allocation of budget to appropriate areas of development and economic development in both the short and long terms.